Metode Peningkatan Literasi pada Pendidikan: Analisis Bibliometrik pada Publikasi 2013 – 2023 - Rasyid Zuhdi; Bagiya Bagiya; Suci Ika Febrianti (JURNAL KRIDATAMA SAINS DAN TEKNOLOGI, 2023)
This study aims to determine the conditions in the range of 2013-2023 related to the scientific map, publication trends, and thematic research coverage of literacy learning methods in education, especially articles published in Scopus, Google Schoolar, and Crossref indexed journals. The research process focused on the following questions: (1). How are literacy improvement methods in education seen from the publication map; (2). What is of interest to academics regarding literacy improvement methods in education? and (3). What topics are often written about in publications related to methods of improving literacy in education? In addition to the research and data sources to be used in the bibliometric analysis, 1200 articles were found through the keywords "literacy, education" in the "article title &; abstract" published in Scopus, Google Schoolar and Crossref indexed journals. To explore and identify the main thematic areas and topics that appear in the publications using keyword occurrence analysis. To support the data analysis and visualization process obtained from Harzing's Publish or Perish and VOSviewer applications. The results of this study show that the method of improving literacy in education is a research trend that has been in great demand in the last 10 years and is still growing. In the visualization section, the high keyword density is presented in 8 clusters, namely: (1) literacy; (2) student; (3) study; (4) ability; and (5) technique. Bibliometric analysis in the form of mapping provides information about the development pattern of publications in the field of literacy in education. These findings provide contributions for future research: 1) The need for holistic research on improving literacy in education; and, 2) the need for in-depth research that focuses on one or several themes that are still rarely studied such as: (1) literacy culture; (2) early age; (3) student response; (4) literacy numeracy; (5) scientific literacy skills; (6) literacy tree; (7) culture and (8) habituation. Keywords: methods, literacy, education